Praktik Budidaya Tanaman Kopi Robusta (Coffea canefora) sesuai Good Agriculture Practice (GAP) di Nagari Situjuah Gadang - Friskia Hanatul Qolby; Latifa, Dara; Sidqi, Muhammad Syakib; Ispinimiartriani, Ispinimiartriani (Universitas Negeri Semarang, 2024)
The agricultural sector is one source of livelihood for the Indonesian population. One of the important sub-sectors is plantations, with coffee being one of the leading commodities. Trends in changing people's lifestyles have resulted in the rapid development of the coffee industry in Indonesia. However, this is not directly proportional to the welfare of farmers in the field, because farmers have minimal knowledge regarding good and correct coffee cultivation techniques so that the quantity and quality of coffee produced is low. This service was carried out using the PALS approach involving coffee farmers who are members of the Palito farmer group in Situjuah Gadang Nagari, Situjuah Limo Nagari District, Lima Puluh Kota Regency, West Sumatra. This service is carried out with the aim of increasing farmers' knowledge and technical skills regarding good and correct coffee cultivation so that they can increase the quantity and quality of coffee produced, as well as increasing the income and welfare of coffee farmers.